Produção e qualidade da batata-doce adubada com fósforo e silício em solo arenoso - Oliveira, Daivyd Silva de (2018)
The sweet potato crop assumes an important role in the agribusiness of vegetables, and responds to the use of mineral fertilizers. The objective of this work was evaluated by the effect of P2O5 and silicon in the production and quality of sweet potatoes. A randomized block design in a 6 x 2 factorial arrangement with six P2O5 doses (0, 60, 120, 180, 240 and 300 kg ha-1 ) at the Federal University of Paraíba, Areia-PB, Brazil, and presence and absence of silicon in the form of potassium silicate (100 ml/20 liters of water) in four replicates. The variables analyzed were the average commercial root mass, number and production of plant-1 roots, total and commercial root yields, fresh and dry shoot mass, starch and ash content in the roots, and leaf P and Si . The average root mass, number and production of plant-1 roots, as total and commercial yields, and fresh and dry leaf mass, with the use of phosphorus and silicon. As quality characteristics, starch and ash were suitable for sweet potatoes. Foliar P content increased with P2O5 doses in the presence of silicon and leaf silicon content was not altered by treatments.